2021
DOI: 10.1016/bs.aecr.2020.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Scales matter: Maximising the effectiveness of interventions for pollinators and pollination

Abstract: Evidence of declines in wild and managed pollinators and pollination services is increasingly being documented around the world. This has driven the development of a wide range of practical management and policy responses which were reviewed in the Intergovernmental science-policy Platform on Biodiversity and Ecosystem Services (IPBES) global assessment of 'Pollinators, Pollination and Food Production'. We take 38 responses from this report as a basis to explore the importance of scale for the effective delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 130 publications
(137 reference statements)
0
7
0
Order By: Relevance
“…That our habitat interventions had no significant effects on the extent of these deficits may be because the uplift in solitary bee numbers resulting from wildflower interventions was not sufficient to increase pollination and reduce deficits measurably. Perhaps the size of the wildflower planting in our landscape context was not sufficient (Faichnie et al, 2021 ), although larger flower plots in some contexts have been found to act as a pollinator sink, reducing visitors to crop flowers (Krimmer et al, 2019 ). Alternatively, the lack of an effect could be because substantial pollination is being delivered by other pollinators that did not respond to our habitat interventions (e.g., bumblebees).…”
Section: Discussionmentioning
confidence: 99%
“…That our habitat interventions had no significant effects on the extent of these deficits may be because the uplift in solitary bee numbers resulting from wildflower interventions was not sufficient to increase pollination and reduce deficits measurably. Perhaps the size of the wildflower planting in our landscape context was not sufficient (Faichnie et al, 2021 ), although larger flower plots in some contexts have been found to act as a pollinator sink, reducing visitors to crop flowers (Krimmer et al, 2019 ). Alternatively, the lack of an effect could be because substantial pollination is being delivered by other pollinators that did not respond to our habitat interventions (e.g., bumblebees).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they can have undesirable impacts such as sheep blow-fly strike caused by species including Lucilia sericata and C. stygia (Morris 2005). Understanding and accounting for the multiple functional services and risks provided by insects associated with landscape features is necessary to ensure management strategies garner broad community support (Faichnie et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As fields cycle through cereals, OSR and field beans, the location of the mass-flowering crops will change but the trees will stay fixed and so the efficacy of a given agroforestry scheme on crop pollination will vary year-to-year (of an order similar to that demonstrated in our simulations where the arable cropping pattern remains fixed and the alley locations are shifted). Spatially optimal configurations of intervention will therefore depend on long-term planning within the landscape (Faichnie et al, 2021). Given hedgerows' greater potential for supporting bumblebee abundance, combining agroforestry with hedgerow planting may generate optimal spatial configurations that promote consistent pollination services through the crop rotation cycle (Eeraerts et al, 2021;Martins et al, 2018).…”
Section: Agroforestrymentioning
confidence: 99%